Comparison of PCB Based Actuator Coils for Untethered Actuation - Erdem Dogus Akkus; Levent Çetin (International Journal of Robotics and Control Systems, 2023)
Recently magnetic actuation has become a versatile tool for manipulation on both the micro and macro scale. Due to the problems arising from scale, conventional electromagnet production methods are insufficient to produce the desired electromagnets to be used for this purpose. To solve the problems arising from this situation, researchers have been forced to work in alternative electromagnet production and application areas and paved the way for PCB-based electromagnetic actuators. For this reason, this article will explain the design principles of PCB planar coils for electromagnetic actuator applications and will provide the basis for later studies to create a coil matrix using this coil design and an actuator that can move ferromagnetic particles or magnets in the plane with this 2D coil matrix. The presented project design steps can be listed as follows; First of all, to be able to design a coil that consists of copper paths on the PCB and can meet expectations (homogeneous magnetic field, high magnetic force/current ratio). PCB coils consisting of square, circular and hexagonal coils are manufactured and various measurements are made. The measured results are consistent with the simulated results proving the accuracy and applicability of PCB coil actuators, and they are highly suitable for a new actuator version. In the tests carried out, coils energized with 1A can provide a maximum field strength of 1400 (A/m) and an average of 900 (A/m) and due to the lack of magnetic core, the created magnetic field has the shape of a bell. In order to overcome this situation, it is foreseen that making studies to increase the working current and, as a more important development, switching from the planar single-layer structure to the structure of two or more layers can increase the magnetic field produced by this type of coils, but this layer increase should take into account the cost and PCB production and application capabilities. should be made available.